Jacobi fields on a Riemann manifold - Bondarenko, V. G. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
Some properties of Jacobi fields on a manifold of nonpositive curvature are considered. As a result, we obtain relations for derivatives of one class of functions on the manifold.